Macrophage Subsets and Death Are Responsible for Atherosclerotic Plaque Formation - Li, Hongxia; Cao, Zhiqiang; Wang, Lili; Liu, Chang; Lin, Hongkun; Tang, Yuhan; Yao, Ping (Frontiers in Immunology, 2022)
Cardiovascular diseases, the notorious killer, are mainly caused by atherosclerosis (AS) characterized by lipids, cholesterol, and iron overload in plaques. Macrophages are effector cells and accumulate to the damaged and inflamed sites of arteries to internalize native and chemically modified lipoproteins to transform them into cholesterol-loaded foam cells. Foam cell formation is determined by the capacity of phagocytosis, migration, scavenging, and the features of phenotypes. Macrophages are diverse, and the subsets and functions are controlled by their surrounding microenvironment. Generally, macrophages are divided into classically activated (M1) and alternatively activated (M2). Recently, intraplaque macrophage phenotypes are recognized by the stimulation of CXCL4 (M4), oxidized phospholipids (Mox), hemoglobin/haptoglobin complexes [HA-mac/M(Hb)], and heme (Mhem). The pro-atherogenic or anti-atherosclerotic phenotypes of macrophages decide the progression of AS. Besides, apoptosis, necrosis, ferroptosis, autophagy and pyrotopsis determine plaque formation and cardiovascular vulnerability, which may be associated with macrophage polarization phenotypes. In this review, we first summarize the three most popular hypotheses for AS and find the common key factors for further discussion. Secondly, we discuss the factors affecting macrophage polarization and five types of macrophage death in AS progression, especially ferroptosis. A comprehensive understanding of the cellular and molecular mechanisms of plaque formation is conducive to disentangling the candidate targets of macrophage-targeting therapies for clinical intervention at various stages of AS.